Parameters associated with short‐ and midterm survival in bridging to lung transplantation with extracorporeal membrane oxygenation. (31st July 2013) - Weig, Thomas; Irlbeck, Michael; Frey, Lorenz; Zwißler, Bernhard; Winter, Hauke; Preissler, Gerhard; Schramm, Rene; Neurohr, Claus; Dolch, Michael E.
Abstract: Patients with terminal lung failure may be bridged to lung transplantation (LTX) by extracorporeal membrane oxygenation (ECMO). With the present shortage of donor organs and the high level of invasiveness of ECMO treatment, appropriate selection criteria for bridge to transplant need to be defined. We report retrospective data from 26 patients on ECMO listed for LTX. Seven patients were successfully transplanted (LTX‐s). Six patients survived until transplantation, but died intra‐ or post‐operatively (LTX‐ns). Thirteen patients died before transplantation (Fail). There was no difference between LTX‐s and the 19 overall non‐survivors (NS) prior to ECMO initiation with regard to demographic data or ventilator parameters except for higher PaO2 /FiO2 in the LTX‐s. Time on ECMO pre‐LTX did not differ in the LTX‐s and LTX‐ns groups. SOFA score was lower in LTX‐s when compared to LTX‐ns before ECMO (p = 0.0155), during bridging (p = 0.028), and right before transplantation (p   =   0.0038). Maximal bilirubin during bridging and bilirubin prior to transplantation was markedly elevated in the LTX‐ns group [4.2 (2.4–4.7) vs. 1.1 (0.8–2.0) mg/dL; p   =   0.0266 and 1.6 (1.2–3.0) vs. 0.5 (0.5–0.5) mg/dL; p   =   0.0047). Bridging to LTX is a challenging but viable option for selected patients. Special consideration should be given to hepatic function.